Trade and Receivables Finance A Practical Guide to Risk Evaluation and Structuring - Jones, Stephen A. (Springer International Publishing, 2018)
Trade and Receivables Finance provides the definitive practical guide to the evaluation and mitigation of risk and the financing of international trade. The traditional method of commercial lending assessment places primary importance on the ability of the borrower to repay the financier. However, this form of evaluation often results in insufficient credit appetite to release the required level of financial support for a company involved in cross border trade. When a trade-related proposition is properly evaluated so that the transactional risks are fully understood and mitigated to an acceptable level, and the source of repayment is identifiable and considered reliable, a well-structured trade and receivables finance facility reduces the risk of default when compared to conventional lending products and can generate additional credit appetite. This book is an authoritative manual built upon more than 42 years of experience in the field of trade finance and will become a constant 'go-to' companion for transaction banking teams, bank relationship managers, specialist client-facing trade and invoice finance specialists, middle and back office trade advisory personnel, credit analysts, alternative market financiers, export development agencies and credit insurers.